Carbon nano materials as gas sensors. (2016) - Elhaes, Hanan; Fakhry, Ahmed; Ibrahim, Medhat
Abstract: The present paper reports the applications of carbon nano materials in the field of sensing with special interest toward gas sensing. The paper will report general introduction about carbon nano materials, then specify to some extent some applications of each type of carbon nano materials. Of course not all types will be included, but the following sections will be covered such that 1.General introduction 2. Carbon nano materials 3. Gas Sensing with Carbon nanomaterials 3-1. Carbon nanotubes 3-2.Multi-walled carbon nanotubes 3-3.Single-walled carbon nanotubes 3-4. Carbon Fibers 3-5. Grapheme and reduced grapheme oxide 4. Conclusion After surveying these classes of materials and describing its role as gas sensor one can conclude the unique physical, chemical and morphological properties of carbon nano materials dedicating it as gas senor even if it applied itself and/or when it blended or fabricated with other materials.